Emerging strategies of blood group genotyping for patients with hemoglobinopathies. Issue 2 (April 2017) - Belsito, A.; Magnussen, K.; Napoli, C.
Abstract: Red cell alloimmunization is a serious problem in chronically transfused patients. A number of high-throughput DNA assays have been developed to extend or replace traditional serologic antigen typing. DNA-based typing methods may be easily automated and multiplexed, and provide reliable information on a patient. Molecular genotyping promises to become cheaper, being not dependent on serologic immunoglobulin reagents. Patients with hemoglobinopathies could benefit from receiving extended genomic typing. This could limit post transfusional complications depending on subtle antigenic differences between donors and patients. Patient/donor compatibility extended beyond the phenotype Rh/Kell may allows improved survival of transfused units of red blood cells (RBC) and lead to reduced need for blood transfusion and leading to less iron overload and reduced risk of alloimmunization. Here we discuss the advantages and limitations of current techniques, that detect only predefined genetic variants. In contrast, target enrichment next-generation sequencing (NGS) has been used to detect both known and de novo genetic polymorphisms, including single-nucleotide polymorphisms, indels (insertions/deletions), and structural variations. NGS approaches can be used to develop an extended blood group genotyping assay system.